2017
DOI: 10.1016/j.ymthe.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-Derived mir-155-Containing Exosomes Suppress Fibroblast Proliferation and Promote Fibroblast Inflammation during Cardiac Injury

Abstract: Inflammation plays an important role in cardiac injuries. Here, we examined the role of miRNA in regulating inflammation and cardiac injury during myocardial infarction. We showed that mir-155 expression was increased in the mouse heart after myocardial infarction. Upregulated mir-155 was primarily presented in macrophages and cardiac fibroblasts of injured hearts, while pri-mir-155 was only expressed in macrophages. mir-155 was also presented in exosomes derived from macrophages, and it can be transferred int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
257
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(267 citation statements)
references
References 47 publications
8
257
0
2
Order By: Relevance
“…Furthermore, miR-126 circulating in plasma has been proposed as a diagnostic marker for myocardial infarction [114]. An additional miRNA, miR-155, was elevated in cardiac macrophages in injured hearts, and its upregulation had a direct impact on fibroblast proliferation in post-MI remodeling [197]. The depletion of miR-155 in macrophages is correlated with decreased levels of CCL2, a chemokine that recruits monocytes, suggesting that macrophage-derived miR-155 expression might serve as a therapeutic target which could suppress both fibrosis and inflammatory responses [135].…”
Section: Inflammatory Responses Post-mi and Ncrnas Derived From Immunmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, miR-126 circulating in plasma has been proposed as a diagnostic marker for myocardial infarction [114]. An additional miRNA, miR-155, was elevated in cardiac macrophages in injured hearts, and its upregulation had a direct impact on fibroblast proliferation in post-MI remodeling [197]. The depletion of miR-155 in macrophages is correlated with decreased levels of CCL2, a chemokine that recruits monocytes, suggesting that macrophage-derived miR-155 expression might serve as a therapeutic target which could suppress both fibrosis and inflammatory responses [135].…”
Section: Inflammatory Responses Post-mi and Ncrnas Derived From Immunmentioning
confidence: 99%
“…This suggests that miRNA-155 might serve as a prognostic marker for cardiac death in post-MI patients [123]. miR-155 is also found in exosomes released by macrophages and this has effects on fibroblasts, which in turn trigger a dysregulation of fibrosis [197]. miR-155 is mainly involved in B- and T-cell receptor signaling, neurotrophin signaling, MAPK signaling, and the cell cycle.…”
Section: Summary: Non-coding Rnas and Immune Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were viewed as evidence that CDC exosomes may switch inert fibroblasts to cells that contribute to cardiac repair. Most recently, Wang et al (55) reported that macrophage-derived exosomes containing mir-155 suppressed fibroblast proliferation and promoted fibroblast inflammation during cardiac injury. Collectively, these findings suggest that exosomes may modify cardiac repair via modulation of fibroblast function.…”
Section: Antifibrotic Activities Of Cdc Exosomesmentioning
confidence: 99%
“…miR-155 also promotes macrophage survival by upregulating the SHIP1-Akt signaling cascade [143]. The increased level of macrophage derived miR-155 acts as paracrine regulator of cardiac fibroblast proliferation as well as inflammatory response following the myocardial infarction induced injury [144]. In contrast, another research group found that miR-155 functions as a negative feedback regulator of immune response by reducing the expression of cytokines by cardiac myocytes during viral infection induced myocarditis [145].…”
Section: Mirna and Cardiomyocytes Injurymentioning
confidence: 99%